Solubility and thermodynamic properties of N-phenylanthranilic acid in Water + Methanol/Ethanol/tert-butanol binary solvents from 283.15 K to 323.15 K. (May 2022) - Luo, Jiaqi; Wang, Yingchen; Shi, Chuncheng; Zhang, Fan; Yu, Qiushuo
Highlights: The solubility of N-phenylanthranilic acid in binary aqueous solvent was determined. The solubility was correlated by Jouyban-Acree model. The Gibbs energy, enthalpy and entropy of dissolution were calculated by the modified van Hoff equation. Abstract: The solubility of N-phenylanthranilic acid in water + tert -butanol/ethanol/methanol was determined by gravimetric method in the temperature range of (283.15 ∼ 323.15) K at atmospheric pressure. Within this temperature range, the solubility increased with increase in the temperature. The descending order of the mole fraction solubility in binary solvents was as follow: water + tert -butanol > water + ethanol > water + methanol. The solubility was correlated by the Jouyban − Acree model. The van't Hoff equation was employed to analyze the thermodynamic properties of dissolution process including the Gibbs energy, enthalpy and entropy. The knowledge of solubility and thermodynamic properties is essential for design of the crystallization and purification of N-phenylanthranilic acid.